Evaluation of Dental Students\' Learning and Study Strategies and Factors Affecting Them in Babol University of medical sciences - SA Seyedmajidi; M Seyedmajidi; F Habibzadeh Bijani; M Kiani (Babol University of Medical Sciences, 2019)
BACKGROUND AND OBJECTIVE: The aim of this study was to investigate and determine the strategies for studying and learning and factors affecting them in dental students of Babol University of Medical Sciences in order to evaluate the students' study and learning skills while entering university. METHODS: This analytical-descriptive study was carried out in 2017 using dental students' opinions of Babol University of Medical Sciences by a questionnaire was comprised of two parts (the first part included demographic information and the second part containing 80 questions in 10 categories). For data analysis, SPSS software was used to comparing mean score between various categories and questions and in each of them in term of demographical variables by parametrical compare mean tests include of repeated measurement, independent t-test, and analysis of variances (ANOVA) and multiple comparisons. The significance level was considered less than 0.05. FINDINGS: Of the 137 participants, 46% (63 men) and 54% (74 women) had a mean age of 22.62 ± 3.19. The highest score was for the skill group with a mean of 3.2 ± 0.39 and the lowest score for the group of will with a mean of 3.12 ± 0.37. The difference between the average score obtained between the skill group and the will and self-regulation groups were significant (P= 0.017 and P= 0.022 respectively). CONCLUSION: According to the results of this study and the obtained scores by the participants which were often in the midrange of acceptable scores (1 to 5), students in most categories of study strategies and learning could be considered weak. Therefore initial assessment while entering the university, monitoring, and continuing education should be provided by the universities' educational development centers to maintain and enhance the level of the categories during the study period.